Pengamplikasian Microsoft Paint dalam Menunjang Minat Belajar Siswa - Sri Hartati; Sri Gustina Lubis; Romaito Gultom; Maya Zefriani Lubis (Al-Ulum: Jurnal Pendidikan Islam, 2020)
The purpose of this study was to determine the effect of microsof paint learning media in supporting students' interest in learning PAI. Knowledge based on religious values in the learning process will make a major contribution to the preparation of students to face the challenges of the times. Through microsoft paint students are able to find ideas, solve problems, or apply what they have learned into life in society. ICT learning is integrated with related values, so students feel that learning is more valuable and enjoyable so that they can make students smarter in the world and afterlife sciences. This research uses field research conducted in real life. The research approach is descriptive qualitative. Data collection techniques in the form of observation, interviews and documentation Keywords: Application Of Microsof Paint, Student Learning Interest.